Sustainable government policy as silver bullet to sustainable business incubation performance In Nigeria - Amat Senin, Aslan (2015)
Business incubation has variously been described as a support programme that assist the early-stage entrepreneurs to develop and stay on their own. Furthermore, business incubation programme has been acknowledged as an economic development tool most countries globally adopted. The aim of this study is to examine the contribution of government policy on the relationship between the critical success factors (CSFs) and incubator performance in Nigeria. The questionnaire method of data collection was used to gather 113 usable questionnaires from incubatees in Nigeria’s business incubators. Structural Equation Modeling (SEM) was performed to determine the result using the Partial Least Square (PLS) Software. Government policy as a moderator did not show a significant moderation relationship between the CSF and incubator performance.